Investigação acerca da manifestação da consciência crítica no estágio supervisionado de ensino - Hanauer, Marcelo José (2022)
This research is linked to the Graduate Program in Education, Doctoral Course in Education, inserted in the Research Line Educational Public Policies, Educational Practices and their Interfaces, of the Federal University of Santa Maria (UFSM). The guiding problem was: how the activities and productions in collaboration in the Supervised Teaching Internship contribute to the construction of the critical conscience of the teacher in training? The general objective was: to investigate the manifestation of critical awareness in the activities and collaborative productions of the Supervised Teaching Internship disciplines, carried out by teachers in training, to evaluate the contributions of these activities and internship productions with regard to the effective development of training and critical theoretical production of the intern student. The theoretical foundation is supported by the specialized literature on: critical awareness (VIEIRA PINTO, 1959; 1960a; 1960b; 1979; 1982; FREIRE, 1980; 1984; 1996), teaching knowledge (TARDIF, 2014), theoretical knowledge and study activity (DAVIDOV, 1988; 1999; ALBERTI, 2011), Supervised Teaching Internship and critical theoretical production at ESE (PIMENTA, 2012; PIMENTA; LIMA, 2017). This is a qualitative research, developed from the methodological guidelines of Research-Action, using as tools to enable the analysis of the data an investigation matrix (responsible for generating the indicators: critical reflection of reality (indicator A), knowledge of the professional training (indicator B) and production of theoretical knowledge (indicator C)), the content analysis proposed by Bardin (2011) and the commercial software Atlas.ti. The specific context of the investigation is the ESE III subject of the Teacher Training for Professional Education course, within the scope of the UFSM Special Graduation Program (PEG). The subjects participating in the research are eight (8) student-interns, one (1) teacher-supervisor of the internship and the researcher. We used documents produced by students (planning and class reports, critical analysis and internship reports) and documents produced by the researcher (field diary and video recordings of the meetings) as data sources. From the corpus of 117 documents produced by intern students during the implementation of collaborative study activities developed in the course, 16 documents were analyzed for planning and reporting of classes, 8 for critical analysis and 8 internship reports. As the main results of the study, we highlight: 1) on the occurrence of indicators A, B and C in the analyzed documents: Indicator A: we verified the accomplishment of a consistent critical reflection of reality, occurrence of production of theoretical knowledge adequate to the purpose of the activities. Indicator B: we verified an intense occurrence of knowledge of professional training, expressed especially by the presence of codes B1, B4 and B5. Indicator C: although with differences and variances of emphasis and intensity, we evidenced in the productions a balance between the indicator codes. This indicates the existence of significant production of theoretical knowledge in the documents considered. 2) as they create opportunities for the development of Transversal Skills in ICT (information, communication, production and security), we believe that the collaborative study activities (synchronous and asynchronous) developed constitute significant contributions to teacher training and can be configured as pedagogical actions molds with potential for educational innovation within the scope of ESE subjects in initial teacher training courses, provided they are replicated with the attention and care employed in this study. 3) by providing the critical reflection of reality, the formation of specific knowledge of teaching and the production of theoretical knowledge, the activities and collaborative productions developed in the ESE III discipline creating material conditions, situations and favorable opportunities to develop: research, dialogue, sharing experiences; the understanding of the specific space of action of the teacher and the challenges that the career will offer; the planning, implementation, reporting and network critical analysis of teaching actions (performed synchronously and asynchronously); study and analytical reflection on the different factors and knowledge involved in the implementation of teaching practice; proposition of new teaching strategies and practices with the intention of qualifying the future educational work to be performed. Based on the results of the analysis, we concluded the following: it was because of the development of analytical capacity on pedagogical praxis, operationalized, generated through interactions (reflections, dialogues, analyses, sharing of experiences) and productions carried out during the activities of collaborative study in a network, which made it possible to detect the manifestation, evolution and improvement of specific characteristics of consciousness in the critical state in the writings of the research subjects. Therefore, the training results achieved with regard to the effective development of consciousness in the critical state, manifest in the productions, are a direct consequence of the pedagogical actions proposed and carried out.